PENINGKATAN KUALITAS BAKSO AYAM DENGAN PENAMBAHAN TEPUNG TALAS SEBAGAI SUBTITUSI TEPUNG TAPIOKA - S. Melia; I. Juliyarsi; A. Rosya (Jurnal Peternakan, 2010)
This research was conducted to evaluate influence of cassava subtitution with calocasia to· quality and self life chicken meat bowl. The experiment design was arranged by campletely randamized block design with 5 treathment and 4 replication. CasstWa and calocasia subtitution level were used as a treatmen. i.e. A(lOO% : 0%),B(75% : 25%), C(50% : 50%), D(25% : 75%), E(O% : 100%). The parameters were evaluated as water value, pH, Total colony count and selflife. The result showed subtitution of cassava with calocasia powder could increase selflife ofchicken meat bowl. The best cambination casstWa and calocasia (0%:100%) was recamanded to produce good quality gelatin ofchicken meat bowl.